CAPAIAN STANDAR PELAYANAN MINIMAL (SPM) BIDANG KESEHATAN KASUS HIPERTENSI DAN DIABETES MELLITUS DI KOTA BANDUNG TAHUN 2020 - yulia astri nurul aliyah (Jurnal Ilmu Pemerintahan Widya Praja, 2020)
This paper describes the implementation and evaluation of the Minimum Service Standards achievements in the health sector in cases of hypertension and Diabetes Mellitus (DM) in Bandung City. Fulfilling SPM is an obligation for both central and regional governments under the mandate of Law 23 of 2014 concerning Regional Government, Government Regulation Number 2 of 2018 concerning Minimum Service Standards, and Minister of Home Affairs Regulation Number 100 of 2018 concerning Implementation of Minimum Service Standards. Using data from reports of 80 community health centres in Bandung City which is the formulation in calculating Minimum Service Standards achievements are based on a formula following the Regulation of the Minister of Health of the Republic of Indonesia Number 4 of 2019 concerning Technical Standards for Fulfilling Basic Service Quality at Minimum Service Standards in the Health Sector. The results are the realization of the percentage of Minimum Service Standards achievements for hypertension cases in Bandung City in 2020 is 18.99%, and the realization of the percentage of Minimum Service Standards achievements for DM cases in Bandung is 115.35%. In the discussion explained why the realization of the Minimum Service Standards achievement of hypertension and DM in Bandung City. The obstacles that arise in fulfilling the Minimum Service Standards achievement in cases of hypertension and DM in Bandung city are following: lack of facilities and infrastructure such as there is no Posbindu PTM Kit due to limited budget. Then, not all community health centre has trained personnel to carry out PANDU PTM activities, there is still low of awareness of recording and reporting as well as reporting and recording are still not following what was designed in the official format. Lastly, not all community health centre has implemented the PANDU PTM programs.